Ethical Perspective of the Future Development of Law - Cerar, Miro (Medicine, Law & Society, 2023)
Law, by its very nature, is human and humane. The humanity of law means that law is a product of man and is intended for man. The humaneness of law, however, means that human dignity and well-being must be the fundamental basis of law. Law, therefore, does not exist without a sufficient ethical foundation. The establishment of a state governed by the rule of law, and a legal culture based on it requires a particularly strong anchoring of law in ethical values. The greatest threats to ethics and law are (1) ethical deficits in areas of society on which law (co-)depends, (2) extreme authoritarian and totalitarian regimes, and (3) autonomous artificial intelligence capable of turning away from humans or even turning against and overcoming humans. In the first two cases, the humaneness of law is critically reduced or even extinguished; in the last case, both the humaneness and the humanity of law are extinguished, which is the worst possible scenario. All these dangers must be recognized in time and adequately averted, and regular efforts must be made to preserve the ethical values and the values of the rule of law.